EP257 Early stage cervical cancer treated by preoperative brachytherapy: prognostic factors ans clinical outcomes. (1st November 2019) - Bataille, B; Escande, A; Le Tinier, F; Parent, A; Bogart, E; Collinet, P; Bresson, L; Narducci, F; Leblanc, E; Lemaire, A-S; Taieb, S; Lartigau, E; et al.
Abstract : Introduction/Background: Optimal management of localized cervical cancer is still controversial. The purpose of this study is to report our experience regarding early stage cervical cancer treated with preoperative brachytherapy (BT) and modified hysterectomy (HT). Methodology: From 2000 to 2013, consecutive patients treated for early stage cervical cancer by preoperative BT and HT were enrolled. They underwent pelvic lymph node assessment by lymphadenectomy prior to BT. Pulse dose rate brachytherapy was performed with either 2D or 3D technique 2D technique. BT aimed to deliver 60 Gray to the clinical target volume, with limited dose to the surrounding tissues, according to GYN-GEC-ESTRO guidelines. Modified HT was performed six to eight weeks after BT. Results: 80 patients were enrolled. 90% had FIGO IB1 stage. Median clinical tumor size was 25 mm (0–40). 61 patients (76%) had a histological complete response. For those with incomplete response, residual tumor was located at the cervix and only one patient had lymphovascular invasion. With a median follow-up of 6.7 years, 16 patients (20%) presented a tumor relapse, with 2 local relapse (3%), 11 regional recurrence, and 9 metastatic relapse. 5-year disease-free survival (DFS) rate and 5-year overall survival (OS) rate were 82% (95% confidence interval [CI]: 71–89) and 88% (95% IC: 78–94) respectively. 24 patients (44%) had grade 2 late toxicity and 10 (13%) had grade 3 late toxicity; with no grade ≥4 toxicities. In univariate analysis, poorer DFS was associated with overweight status (≥25 kg/m 2, hazard ratio [HR]: 3.05, 95% CI: 1.20–7.76, p=0.019) and MRI tumor size of >3 cm (HR: 3.05, 95% CI: 1.23–7.51, p=0.016). Conclusion: Preoperative BT followed by HT may be safe and effective for patients with early stage cervical cancer. Since poorer outcomes were associated with overweight and tumor size >3 cm, more agressive treatment should be considered for those patients. Disclosure: Nothing to disclose.